PENGARUH BRAND AWARENESS, KERAGAMAN PRODUK DAN IMPULSE BUYING TERHADAP KEPUTUSAN PEMBELIAN PADA WIZZMIE MERR SURABAYA - Wihardono, Laurensia Diana Friscarona; Ayu, Stephanie Astrid (STIE Mahardhika, 2025)
The food and beverage industry in Indonesia, particularly the spicy food business, is growing rapidly and significantly contributing to the economy. Wizzmie, a new spicy noodle outlet in Surabaya, is a rapidly developing business. This study examines the impact of brand awareness, product diversity, service quality, and impulse buying on purchasing decisions at Wizzmie Merr Surabaya. This quantitative study surveyed 100 respondents who had made at least two direct purchases at Wizzmie Merr Surabaya. Data was collected via questionnaires distributed through Google Forms and on-site, then analyzed using SPSS version 26.0. Validity and reliability tests confirmed the suitability of all variables, while normality, multicollinearity, and heteroscedasticity tests met the necessary assumptions. The multiple linear regression model resulted in the equation: Y = 1.151 + 0.761X1 + 0.135X2 + 0.073X3 + 0.152X4, with an adjusted R-square value of 56.5%, indicating a moderate influence of the independent variables on purchasing decisions. The findings show that brand awareness (X1) significantly affects purchasing decisions (t-value 7.623 > t-table 1.985, significance 0.000 < 0.050). However, product diversity (X2), service quality (X3), and impulse buying (X4) do not have significant effects, with their t-values and significance levels exceeding the threshold. These results highlight that brand awareness is the most critical factor in influencing consumer purchasing decisions at Wizzmie Merr Surabaya, while other factors play a less significant role.